First-Principles Calculation of Conductivity of Ce-C Codoped SnO2 Contacts - Can Ding; Zhenjiang Gao; Xing Hu; Zhao Yuan (Advances in Condensed Matter Physics)
The contact is the core element of the vacuum interrupter of the mechanical DC circuit breaker. The electrical conductivity and welding resistance of the material directly affect its stability and reliability. AgSnO2 contact material has low resistivity, welding resistance, and so on. This material occupies an important position of the circuit breaker contact material. This research is based on the first-principles analysis method of density functional theory. The article calculated the lattice constant, enthalpy change, energy band, electronic density of state, charge density distribution, population, and conductivity of Ce, C single-doped, and Ce-C codoped SnO2 systems. The results show that Ce, C single doping, and Ce-C codoping all increase the cell volume and lattice constant. When the elements are codoped, the enthalpy change is the largest, and the thermal stability is the best. It has the smallest bandgap, the most impurity energy levels, and the least energy required for electronic transitions. The 4f orbital electrons of the Ce atom and the 2p orbital electrons of C are the sources of impurity energy near the Fermi level. When the elements are codoped, more impurity energy levels are generated at the bottom of the conduction band and the top of the valence band. Its bandgap is reduced so conductivity is improved. From the charge density and population analysis, the number of free electrons of Ce atoms and C atoms is redistributed after codoping. It forms a Ce-C covalent bond to further increase the degree of commonality of electrons and enhance the metallicity. The conductivity analysis shows that both single-doped and codoped conductivity have been improved. When the elements are codoped, the conductivity is the largest, and the conductivity is the best.